Comparative study of the inverse versus normal bicontinuous cubic phases of the β-d-glucopyranoside water-driven self-assemblies using fluorescent probes. Issue 1 (21st December 2015) - Zahid, N. Idayu; Abou-Zied, Osama K.; Nabila Saari, N. A.; Hashim, Rauzah
Abstract : This work investigates the head group region of the inverse and normal bicontinuous cubic phases ( Ia 3 d space group) of the glucopyranoside/water system using 2-(2′-hydroxyphenyl)benzoxazole and its derivatives as fluorescent probes. Abstract : Lipid/water systems displaying cubic symmetry are pervasive in biomembranes and important in technological applications such as nanoparticle templating and drug-delivery systems. Herein, we characterized the inverse bicontinuous cubic phase of the 2-hexyl-decyl-β-d -glucopyranoside/water system and the normal bicontinuous cubic phase of the octyl-β-d -glucopyranoside/water system. We investigated the head group region using 2-(2′-hydroxyphenyl)benzoxazole (HBO) and two of its derivatives as fluorescent probes. In the inverse phase, the syn -enol tautomer of HBO dominates the signal. This is attributed to the very narrow water channels (diameter of 2.3 nm) which support the formation of a hydrogen bond between the OH group of HBO and oxygen from the sugar units. A small contribution from the HBO anion species was also detected and is proposed to be the result of a hydrogen ion abstraction by the sugar units. In contrast, fluorescence of HBO in the normal phase is dominated by the keto tautomer with some contribution from the anionic form. Fluorescence lifetimes indicate that efficient excited-state intermolecular proton transfer, facilitated by the confined water molecules, yields the keto tautomer. This confined water contributes also toward the stability of the anion species in both cubic phases. Attaching a C4 (HBO-C4 ) or a C8 (HBO-C8 ) alkyl chain to the phenyl ring of HBO yielded similar results which indicates that the HBO moiety occupies the same position in the hydrophilic region, regardless of the attached hydrophobic chain. The two detected forms of HBO in each lipid suggest a degree of local heterogeneity that was also observed in the measured two fluorescence lifetime components. The current study is anticipated to contribute toward a better understanding of drug–lipid interaction which is important for drug absorption by the cell membrane.